A didactic tool for gender-sensitive practices in design education - Reina, Marta Isabella (My University, 2017)
This article presents the results of experimental research conducted as part of a project concerning a didactical tool named “Design/Gender/Design” which is to be used to introduce gender issues into the training of young designers. The article describes the experimental set-up and students’ results. The intention is to stimulate a discussion about how design should integrate a gender perspective in theory and practice. By observing design as a process of exchange of values and meanings, we aim to understand its responsibility in the diffusion of gender stereotypes, how these gender stereotypes are incorporated into design projects and how they act within and through them, as well as through the sensitivities of designers. Students were asked to respond to design questions concerning gender in order to compile categories of signs targeted at her, him and everybody and covering different aspects (e.g. shapes and sizes, colours, patterns and textures, and typographic elements). Being typical of action research, the experiment allowed students to reflect on the use of gender codes in design and it provided data for researchers to verify assumptions regarding those associations which are implicit when gender is a variable in the design process.
Keywords: design education; Gender stereotypes; Geschlechterstereotyp; post-structuralism; Poststrukturalismus; reflective practices; visual Criticism; ddc:303